Employers’ perception on important employability skills in the manufacturing industry - Shiau, Wei Chan; Ahmad, M.F.; Zaman, Izzuddin; Woan, Shin Ko (Science Publishing Corporation, 2018)
Employability skills are among the important soft skills that should be acquired by employees in the industrial sector today. Unfortunately, Malaysian graduates do face obstacles when looking for employment upon graduation due to the absence of employability skills among them. The main aim of this study is to identify employers’ perceptions of the most important employability skills in the manufacturing industry. The study is also aimed to determine the differences between the important employability skills from the perspective of employers based on their gender, their company’s size, and types of companies in the manufacturing industry. In this study, a total of 182 employers from the manufacturing industry in Batu Pahat were chosen randomly. Questionnaires were administered to the employers. The data generated were statistically analysed using descriptive and inferential analyses. The analysis shows that employers’ perception of the most important employability skills in manufacturing industry is communication skills. The independent variables chosen are gender, company size, and types of manufacturing sector, while the dependent variable is the perceptions of important employability skills in the manufacturing industry. Results show that the perceptions of important employability skills in the manufacturing industry have no significant difference according to employers’ gender and type of manufacturing sector, but there is a significant difference for company size. This quantitative study provides key insights that enable future employees to have more understanding of the employment demand in the manufacturing industry nowadays and for employees to develop their employability skills before getting ready to enter the labour market.